2012
DOI: 10.1007/s10120-012-0154-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of Roux-en-Y and Billroth-I reconstruction after laparoscopic distal gastrectomy

Abstract: Background Laparoscopic distal gastrectomy (LDG) is an established procedure for the treatment of early gastric cancer. Roux-en-Y (R-Y) or Billroth-I (B-I) reconstruction is generally performed after LDG in Japan. The aim of this retrospective cohort study was to compare the effectiveness of R-Y and B-I reconstructions and thereby determine which has better clinical outcomes. Methods We analyzed data from 172 patients with gastric cancer who underwent LDG. Reconstruction was done by R-Y in 83 patients and B-I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 35 publications
2
43
1
Order By: Relevance
“…Studies have shown beneficial outcomes in terms of less reflux symptoms and less gastric remnant gastritis [81,82] . These findings persist in long-term follow-up [83] . However, patients did not differ in terms of quality of life [84] .…”
Section: Reconstruction Techniquementioning
confidence: 58%
“…Studies have shown beneficial outcomes in terms of less reflux symptoms and less gastric remnant gastritis [81,82] . These findings persist in long-term follow-up [83] . However, patients did not differ in terms of quality of life [84] .…”
Section: Reconstruction Techniquementioning
confidence: 58%
“…Several studies have reported high incidences of gallstone formation after open gastrectomy without vagal nerve preservation [8,9,10]. Our previous study found that the resection of the CB is associated with a slightly, but not significantly higher incidence of gallstone formation only after R-Y reconstruction [11]. We therefore focused on patients who underwent R-Y reconstruction in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, patients who undergo gastrectomy for gastric cancer followed by RY reconstruction have the possibility of experiencing copper deficiency when food bypasses the duodenum and proximal jejunum, as the main regions engaged in copper absorption. Although some reports have described RY reconstruction after gastrectomy for gastric cancer as offering several advantages [10][11][12] , none seem to have assessed the serum copper state of patients who have undergone gastrectomy followed by RY reconstruction for gastric cancer. This study therefore investigated and analyzed the serum copper state in these patients.…”
Section: Introductionmentioning
confidence: 99%